2006
DOI: 10.1007/s10661-006-0799-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Non-Cancer Health Risk from Eating Cassava Grown in Some Mining Communities in Ghana

Abstract: Food crops such as cassava, cocoyam and other tuber crops grown in mining communities uptake toxic or hazardous chemicals such as arsenic, and cadmium, from the soil. Cassava is a stable food for Ghanaians. This study evaluated human health risk from eating cassava grown in some mining communities in Ghana such as Bogoso, Prestea, Tarkwa and Tamso, which are important mining towns in the Western Region of Ghana. The study evaluated cancer and non-cancer health effects from eating cassava grown in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Furthermore, Amasa (1975), AmonooNeizer and Amekor (1993), and Adomako et al (2010) have reported high concentrations of As in food items such as orange, sugar cane, cassava, and rice from mining regions in Ghana. According to Obiri et al (2006), high arsenic in food crops grown in miningcontaminated areas of Ghana can cause adverse effects to human health. In this way, in Ghana, Asante et al (2007) who found the same high concentrations of arsenic in human urine samples from residents of the mining town of Tarkwa and from non-mining town of Accra suggested that human contamination of arsenic has another source, possibly foods.…”
Section: Health Hazard Linked To High-as Water In Africamentioning
confidence: 99%
“…Furthermore, Amasa (1975), AmonooNeizer and Amekor (1993), and Adomako et al (2010) have reported high concentrations of As in food items such as orange, sugar cane, cassava, and rice from mining regions in Ghana. According to Obiri et al (2006), high arsenic in food crops grown in miningcontaminated areas of Ghana can cause adverse effects to human health. In this way, in Ghana, Asante et al (2007) who found the same high concentrations of arsenic in human urine samples from residents of the mining town of Tarkwa and from non-mining town of Accra suggested that human contamination of arsenic has another source, possibly foods.…”
Section: Health Hazard Linked To High-as Water In Africamentioning
confidence: 99%
“…Gold mining in Ghana has been the largest foreign exchange earner since pre-independence, with gold export earnings rising from US$ 107.9 million to US$ 744.2 million between 1985and 1989(Obiri et al 2006. The main gold prospects in Ghana occur at Obuasi and Konongo in the Ashanti region, and at Tarkwa, Prestea and Bogosu in the western region (Oberthur et al 1997;Smedley 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse health effects have also been linked to As in food crops grown in mining-contaminated areas of Ghana (Obiri et al, 2006). and were thought likely to be of localised occurrence.…”
Section: Introductionmentioning
confidence: 99%